Educational leadership from the perspective of complexity - Rosabal Vitoria, Satya; Cerdas Montano, Virginia (Revista Saberes Educativos, 2025)
The current Costa Rican Educational Policy includes the paradigm of complexity in its philosophical framework, which poses a challenge for the people who execute these policies in educational centers. This article presents a study that addresses the role of the director, the diverse contexts where his actions are carried out, his management practices, the challenges he/she faces, the leadership styles he/she exercises and the knowledge he/she requires to be consistent with the current paradigmatic vision. This study is qualitative in nature and is developed from an exploratory-descriptive perspective. An investigation is proposed through an interview and two focus groups based on a guide of open questions, designed and contextualized for each of the participating populations, made up of twenty-seven people immersed in various areas of the educational system. Among the main conclusions, the following stand out: the figure of the director in his role as pedagogical leader is a key element in the processes of organizational change and transformation and the challenges in the management of educational organizations are multifactorial in nature and demand knowledge to manage uncertainty, promote dialogue, energize disruptive, dynamic, flexible and contextualized processes to redefine educational leadership from the paradigm of complexity.